Ethanol sensing characteristics of Sn-doped ZnO tetrapods sensor - Theerapong Santhaveesuk (2018)
Sn-doped ZnO tetrapods (T-SnZnO) were successfully synthesized using a simple thermal oxidation reaction method. Zn powder with 20 mol% of Sn powder was used as raw material and synthesized at temperature of 1,000°C under normal atmosphere. FE-SEM images revealed that the T-SnZnO exhibited a four symmetry legs with the length of 1.94±0.42 μm and the width of 260±40 nm. EDS analysis confirmed that the tetrapods contain small amount of Sn. XRD analysis indicated that the tetrapods exhibited a wurtzite hexagonal ZnO structure corresponded to Raman results. The lattice parameters a and c were 3.2494 Å and 5.2057 Å, respectively. The T-SnZnO were fabricated as ethanol sensor and tested with ethanol concentration of 50, 200, and 1,000 ppm at operating temperature between 280°C-340°C by observing I-V curve of the sensors. The sensor response increased as the increasing of the operating temperature and the ethanol concentration. Moreover, the enhancement of ethanol sensor response was observed, and the highest sensor response of 30.4 was detected at 340°C. The sensor response was higher than those of ZnO tetrapods, TiO2-ZnO tetrapods, ZnO nanowires, and TiO2-ZnO nanowires sensors. © (2013) Trans Tech Publications, Switzerland.